Glutathione PEGylated liposomal methylprednisolone (2B3-201) attenuates CNS inflammation and degeneration in murine myelin oligodendrocyte glycoprotein induced experimental autoimmune encephalomyelitis - Lee, De-Hyung; Roetger, Caroline; Appeldoorn, Chantal C. M.; Reijerkerk, Arie; Gladdines, Werner; Gaillard, Pieter J.; Linker, Ralf (Journal of Neuroimmunology, 2014)
Methylprednisolone (MP) pulses are the mainstay for relapse therapy in multiple sclerosis (MS). To improve the efficacy of treatment and reduce the side effects of MP, a long circulating brain-targeted formulation was developed; glutathione polyethylene glycol (PEG)ylated liposomal MP (2B3-201). Here we investigate the efficacy of 2B3-201 in murine myelin oligodendrocyte induced experimental autoimmune encephalomyelitis (MOG-EAE), an animal model mimicking inflammatory features and neurodegenerative aspects of MS. After disease onset, mice were randomized to receive either saline, three injections of free MP (high dose MP, 100mg/kg i.v.), two injections of free MP (low dose MP, 10mg/kg; i.v.), or two injections of 2B3-201 (10mg/kg i.v.). Treatment with a low dose of 2B3-201 significantly reduced the severity of EAE as compared to saline control, similar to treatment with high dose free MP, while a low dose of free MP was not effective. In a histological analysis of the spinal cord, treatment with 2B3-201 significantly decreased T cell as well as macrophage/microglia infiltration in the CNS by about 50%. Moreover, application of a low dose of 2B3-201 or a high dose of free MP reduced the amount of astrocyte activation as well as the extent of axonal loss and also demyelination in spinal cord lesions as compared to low dose MP or sham treatment. In summary, in the murine MOG-EAE model of MS, a glutathione PEGylated liposomal formulation of MP (2B3-201) is clinically and histologically as effective as free MP at one tenth of the dosage as well as at a lower application frequency and clearly more effective than the same dosage of free MP. These positive proof-of-concept efficacy studies warrant further development of 2B3-201 for the treatment of neuroinflammatory conditions such as MS.
EVALuna2:22300